Analysis of Polybrominated Diphenyl Ethers and Lipid Composition in Human Breast Milk and Their Correlation with Infant Neurodevelopment - Ming-Hsien Tsai (MDPI AG, 2021)
Breastfeeding is recommended over formula feeding, but human breast milk (HBM) composition varies and can be affected by food additives. Whether flame-retardant polybrominated diphenyl ethers (PBDEs) found in HBM interact with lipid components of HBM to impede infant neurodevelopment is a critical public health issue. Using lipidomic analysis, we examined the association of PBDEs in HBM and HBM lipid components with infant neurodevelopment. HBM samples (n = 100) were collected at the beginning stage of breastfeeding and analyzed for 30 PBDE congeners as well as a group of lipid components by using high-resolution gas chromatography, mass spectrometry, and liquid chromatography time-of-flight mass spectrometry. Infants were examined at 8 to 12 months of age by using the Bayley-III to assess neurodevelopment. A total of seven PBDEs, 35 lipids, and 27 fatty acids in HBM showed significant associations with Bayley-III scores. Multivariate analysis confirmed that these candidate PBDEs and lipid components were significant predictors of infant neurodevelopment. Eicosapentaenoic acid and docosapentaenoic acid in HBM showed no association with infant neurodevelopment in the general Taiwanese population. While certain PBDEs may play a role, our findings indicate that the lipid components of HBM are directly important for infant neurodevelopment.